Building nursing and midwifery leadership capacity in the Pacific. (29th June 2016) - Rumsey, M.; Catling, C.; Thiessen, J.; Neill, A.
Abstract : Aim: The Australian Award Fellowship Program aimed to strengthen nursing and midwifery leadership and capacity in developing countries in the Pacific. Background: It is necessary to build an optimal global health workforce, and leadership and mentorship are central to this need. This is especially important in small island states such as the Pacific who have limited capacity and resources. Introduction: This health system strengthening program addressed quality improvement in education, through the mentorship of potential nursing and midwifery leaders in the South Pacific Region. Methods: Program participants between 2013 and 2015 were interviewed. Data were audio‐taped, transcribed and analysed thematically using an inductive process. Results: Thirty‐four nurses and midwives from 12 countries participated. There were four main themes arising from the data which were: having a country‐wide objective, learning how to be a leader, negotiating barriers and having effective mentorship. Discussion: Our study showed that participants deemed their mentorship from country leaders highly valuable in relation to completing their projects, networking and role modelling. Similar projects are described. Limitations: The limitation of this study was its small size. There is a need to continue to build the momentum of the program and Fellows in each country in order to build regional networks. Conclusions and implications for nursing and midwifery: The Program has provided beneficial leadership education and mentorship for nurses and midwives from Pacific countries. It has provided a platform to develop quality improvement projects in line with national priorities. Implications for health policy: Global aid programs and the recipients of the program would benefit from comparable health strengthening approaches to nursing and midwifery in similar developing countries.